Place Identity of Residential Enyironment in Iraqi Contemporary Architectural rrends and its Impact on Academic Architectural product - Al-Duji, Mumtaz Hazem; Taha, Saba Ibrahim; Al - Sanjari, Hassan Abdul Razzaq (Iraqi Journal of Architecture and Planning, 2018)